Modulating gut dysbiosis and mitochondrial dysfunction in oxazolone-induced ulcerative colitis: the restorative effects of β-glucan and/or celastrol - Omnia Safwat El-Deeb; Rasha Osama El-Esawy; Hanan Alsaeid Al-Shenawy; Heba Bassiony Ghanem (Taylor & Francis Group, 2022)
Objectives Microbiome-Mitochondria interaction is gaining a significant attention; thus, studying its mechanism emerges as a must to provide restorative lines in managing diseases. The aim is to study the mechanistic effects of β-Glucan and/or Celastrol in oxazolone-induced ulcerative colitis (UC).Methods 75 Wistar rats were allocated into 5 equal groups. Group I: control group. Group II: UC group, Group III: β-Glucan-treated UC group, Group IV: Celastrol-treated UC group & Group V: mutual treatment group. All groups were subjected to the detection of free fatty acid receptor 2 (FFAR-2) and peroxisome proliferator-activated receptor gamma co-activator1α (PGC-1α) mRNA gene expressions. Citrate synthase (CS) activity, mitochondrial membrane potential (MMP), ATP concentration, reactive oxygen species (ROS) were detected. Trimethylamine N-oxide (TMAO) concentration was measured.Results After treatment we monitored significant upregulation of FFAR-2 and PGC-1α mRNA expression. Likewise, ATP level and CS activity were significantly increased. On the contrary, there was a significant lessening in ROS and TMAO levels with improvement of MMP.Conclusion Mutual use of β- Glucan and Celastrol had a greater effect than each alone against UC, which is considered a novel finding highlighting the ameliorative effects of this combined treatment in modulating Microbiome/Mitochondria axis, thus launching promising avenues for UC.